The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/2684836
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-Based Detection and Clinical Evaluation for Helicobacter pylori Resistance to Clarithromycin or Levofloxacin and the Genotype of CYP2C19 in 1083 Patients

Abstract: Background. Helicobacter pylori (H. pylori) is one of the most frequent and persistent bacterial infections that affect nearly half of the world's population. Antibiotic resistance is a constantly evolving process and local surveillance of antibiotic resistance is warranted to guide clinicians in their choice of therapy. The aim of this study was to establish a microarray-based detection to identify H. pylori infection, clarithromycin and levofloxacin susceptibility, and CYP2C19 genetic polymorphism and guide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
7
1
1
Order By: Relevance
“…Microarray is a rapid, high-throughput detection method [ [115] , [116] , [117] ], which can reverse transcription of viral RNA and produce a specific probe labeled cDNA. The cDNA was then loaded into each well and hybridized with solid-phase oligonucleotides on the Microarray, which is then washed to remove the free DNAs.…”
Section: Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray is a rapid, high-throughput detection method [ [115] , [116] , [117] ], which can reverse transcription of viral RNA and produce a specific probe labeled cDNA. The cDNA was then loaded into each well and hybridized with solid-phase oligonucleotides on the Microarray, which is then washed to remove the free DNAs.…”
Section: Detection Methodsmentioning
confidence: 99%
“…In addition, there are many kinds of this method, so it is difficult to establish a unified quality standard, which limits its clinical application. [ 116 ] ELISA At present, ELISA is commonly used in clinical detection of viruses, which is based on the specific binding of antigen and antibody. The procedure of this method is simple, because there is no need to use the second antibody, it can avoid the interaction reaction, high sensitivity and high specificity, and the antigen does not need to be purified in advance, so it can be applied to relatively impure samples, and the data reproducibility is very high.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…Frye et al have developed a DNA microarray capable of detecting all antimicrobial resistance genes found at the National Center for Biotechnology [93]. Furthermore, a microarray has been use to identify Helicobacter pylori resistance to clarithromycin and levofloxacin, as well as to detect CYP2C19 polymorphism [94]. It is reported that this microarray can be used for individual therapy detection as it has high specificity, reproducibility, and sensitivity [78].…”
Section: Microarrays and Drug Resistancementioning
confidence: 99%
“…The microarray layout is shown in Figure 1a. Microarrays were prepared as previously described by our research group [37].…”
Section: Microarray Preparationmentioning
confidence: 99%